Durum wheat in the Mediterranean Rim: historical evolution and genetic resources - Martínez-Moreno, Fernando; Solís, Ignacio; Noguero, Dolores; Blanco, Antonio; Özberk, İrfan; Nsarellah, Nasserlehaq; Elias, Elias; Mylonas, Ioannis; Soriano, Jose Miguel (Genetic resources and crop evolution, 2020)
Durum wheat ( Triticum turgidum L. subsp. durum (Desf.) van Slageren) is an important crop in the Mediterranean Rim, and it is deeply rooted in the history and tradition of this region. Recently, several studies that examined DNA markers on Mediterranean landrace collections have successfully elucidated the pathways of this crop across the Mediterranean Rim, but the historical frame is still rather diffuse. This paper aims at tracing the historical evolution of durum wheat throughout the Mediterranean Rim since its commencement as a crop until present times. A search was carried out through archaeological references where durum wheat remains were found. Historical descriptions about cultivation of this crop, references to products made from its grain, and articles interpreting DNA marker information from Mediterranean landraces were also consulted. The present article also examines the currently available durum wheat genetic resources. Durum wheat was domesticated in the Levant area. Phoenicians, Greeks, and above all Romans were active in the expansion and success of durum cultivation in all Mediterranean Rim that started displaced emmer by the mid first millennium BCE. Early Arab empire expanded in the area of durum wheat cultivation promoting food types based on semolina (dry pasta and couscous). Up to 1955 most durum areas in this area were planted with landraces, but several breeding programs were initiated in Italy, and later at CIMMYT and at ICARDA. Landrace collection and conservation efforts were carried out along the Mediterranean Rim countries to preserve the legacy of this crop.